Old drugs, novel ways out: Drug resistance toward cytotoxic chemotherapeutics. (September 2016) - Wijdeven, Ruud H.; Pang, Baoxu; Assaraf, Yehuda G.; Neefjes, Jacques
Abstract: Efficacy of chemotherapy in the treatment of distinct malignancies is often hampered by drug resistance arising in the tumor. Understanding the molecular basis of drug resistance and translating this knowledge into personalized treatment decisions can enhance therapeutic efficacy and even curative outcome. Over the years, multiple drug resistance mechanisms have been identified that enable tumors to cope with the damage instigated by a specific drug or group of anti-tumor agents. Here we provide an overview of the molecular pathways leading to resistance against conventional anti-cancer drugs, with emphasis on the utility of these pathways for rational selection of treatments for individual cancer patients. We further complement the review by discussing the pitfalls and difficulties in translating these findings into novel treatment strategies for cancer patients.